Studi Kehilangan Volume Batugamping pada Kegiatan Peledakan dan Crushing di PT. Yusrina Borneo Quantum Kecamatan Loakulu Kabupaten Kutai Kartanegara, Provinsi Kalimantan Timur - Muhammad Aji Satria Mandiri; Revia Oktaviani; Agus Winarno; Tommy Trides; Windhu Nugroho (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
Blasting and crushing are essential stages in the limestone mining process; however, both stages may contribute to material volume loss due to technical factors and geological conditions. This study aims to analyze the blasted volume, crushed volume, and the amount of volume loss occurring throughout these processes. The research utilizes primary data including blasting geometry, blasting patterns, crushing production, and secondary data such as regional geology and equipment specifications. Based on 15 blasting activities conducted from October to December 2024, the total blasted volume reached 71,691 tons with an average powder factor of 0.23 kg/m³. Meanwhile, the total volume produced from secondary crushing was 71,575 tons. The comparison indicates volume loss influenced by suboptimal fragmentation, rock characteristics, work efficiency of the crushing unit, and operational constraints in the field. The results of this study are expected to serve as a reference for optimizing blasting design and crushing operations to minimize volume loss and improve overall mining productivity.